Closed Circuit Television (CCTV) Based Security System in Realizing Electronic Government in Makassar City - Syailalhikma, Yunira; Haning, Muhammad Thahir; Abdullah, Muhammad Tang (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2023)
The current trend of using technology in public organizations must be addressed. The electronic government initiative in Indonesia was introduced through Presidential Instruction Number 6 of 2001 on April 24, 2001, concerning Telematics (Telecommunication, Media, and Informatics), which states that government officials must use telematics technology to support good governance and speed up the democratic process. This research was conducted in Makassar City. The number of people with vehicles in Makassar City, as well as staff employees or CCTV operators who work in 3 (agencies), namely the Communication and Information Service, the Transportation Service and the Makassar Big City Resort Police are huge, but due to the efficiency of time and energy, the author took The sample used non-probability sampling with an accidental sampling technique for people with the number of vehicles in Makassar City and with a purposive sampling technique for employee staff and CCTV operators from the three agencies so that 139 Respondents were obtained, where the author then distributed questionnaires to respondents directly. The research results state that the Informational Disposition states that the Closed Circuit Television (CCTV) based security system in Makassar City has fulfilled the first quadrant category of the e-government initiative framework by Nour et al (2008), namely informational disposition. Transactional disposition states that respondents agree that the Closed Circuit Television (CCTV)-based security system in Makassar City meets the second quadrant category of the e-government initiative framework by Nour et al. (2008), namely transactional disposition. The consultation disposition states that the Closed Circuit Television (CCTV)-based security system in Makassar City has fulfilled the third quadrant category of the e-government initiative framework by Nour et al. (2008), namely the consultation disposition. The participatory disposition states that respondents strongly agree that there is equity and that there is democratic Responsiveness, Public Accountability, efficiency/economy, and effectiveness/ quality of service in the Closed Circuit Television (CCTV) based security system in Makassar City. Therefore, the Closed Circuit Television (CCTV) based security system in Makassar City has fulfilled the fourth quadrant category of the e-government initiative framework by Nour et al. (2008), namely a participatory disposition.